2008
DOI: 10.1111/j.1460-9568.2008.06415.x
|View full text |Cite
|
Sign up to set email alerts
|

Myelinated, synapsing cultures of murine spinal cord – validation as an in vitro model of the central nervous system

Abstract: Research in central nervous system (CNS) biology and pathology requires in vitro models, which, to recapitulate the CNS in vivo, must have extensive myelin and synapse formation under serum-free (defined) conditions. However, finding such a model has proven difficult. The technique described here produces dense cultures of myelinated axons, with abundant synapses and nodes of Ranvier, that are suitable for both morphological and biochemical analysis. Cellular and molecular events were easily visualised using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 75 publications
(131 reference statements)
3
74
0
Order By: Relevance
“…In general, the maximum percentage of myelination in the cultures ranges from 2%-10% after 28 DIV as many of the fibers generated in culture are interneurons. Previously, we have demonstrated that myelin is compacted 25 and formed correctly with the correct location of nodal proteins in these cultures. 24 Comparisons were made to a positive control of cultures grown on a PLL-coated glass coverslip (to assure us that the cultures are differentiating correctly), and the following PLL-coated test substrates: PCL (low (L) and high (H) Mw), PC, PMMA, PS, PLLA, and PDMS (Fig.…”
Section: Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…In general, the maximum percentage of myelination in the cultures ranges from 2%-10% after 28 DIV as many of the fibers generated in culture are interneurons. Previously, we have demonstrated that myelin is compacted 25 and formed correctly with the correct location of nodal proteins in these cultures. 24 Comparisons were made to a positive control of cultures grown on a PLL-coated glass coverslip (to assure us that the cultures are differentiating correctly), and the following PLL-coated test substrates: PCL (low (L) and high (H) Mw), PC, PMMA, PS, PLLA, and PDMS (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Myelin ensheathment observed in these cultures is similar to myelination and sheath formation in vivo. [23][24][25][26] One important feature of the myelinating culture is ensuring that the neurite density is comparable between , markers of increasing oligodendroglial maturity at both 7 DIV and 14 DIV, with the percentage of A2B5 + cells and NG2 + cells calculated from a total cell number as indicated by DAPI (blue) staining. The total coverage of O4 + processes was also calculated and divided by the total DAPI count to give a ratio of O4 + coverage to total cell number.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations